Differential signaling circuits in regulation of ultraviolet C light-induced early- and late-phase activation of NF-κB - Wu, Shiyong (2010)
Ultraviolet C light (UVC) induces NF-κB activation via a complex network. In the early phase (4-12 h) of irradiation, NF-κB activation is accompanied with IκBα reduction via a translation inhibition pathway. In the late phase of UV-induced NF-κB activation (16-24 h), the IκBα depletion is a combined result of regulation at both transcriptional and translational levels. However, the NF-κB activation appears to be independent of the level of IκBα. In this review, we will discuss the multiple signaling circuits that regulate NF-κB activation during the early and late phases of UVC-irradiation.